Kemandirian Fiskal Kota Palangka Raya : Analisis Kemampuan Keuangan Daerah Tahun 2021 - 2024 - Solihin, Danna (RJABM (Research Journal of Accounting and Business Management), 2025)
This research aims focuses on examining the financial capacity of Palangka Raya City during  2021–2024 period using the Share, Growth, and Elasticity Index approaches. Regional financial capacity serves as an important indicator in assessing the level of fiscal independence and the extent to which a region can reduce its dependence on central government transfers. The researche relies on secondary data sourced from BPS, BPKAD, and the Palangka Raya City Budget (APBD) documents, which were then analyzed using a descriptive quantitative method. The results indicate that the Share Index of Palangka Raya’s Locally-Generated Revenue (PAD) showed a declining trend from 22.99% in 2021 to 14.08% in 2024, reflecting the relatively low contribution of PAD to total revenue. The PAD Growth Index fluctuated significantly, with a sharp increase in 2021 (60.61%) due to post-pandemic economic recovery, followed by contractions in 2022 (-4.29%) and 2023 (-31.99%), before returning to positive growth in 2024 (5.96%). Meanwhile, the Elasticity Index demonstrates that PAD is still able to respond to economic growth, although its contribution remains relatively small. Overall, the Regional Financial Capacity Index (IKK) averaged only 0.22, placing it in the low category. This finding highlights the city’s strong dependence on central government transfers, indicating that Palangka Raya’s fiscal independence remains far from optimal. The study recommends optimizing PAD through strengthening the tax base, improving regional asset management, and developing leading economic sectors to enhance the city’s fiscal capacity in a sustainable manner.